2023
DOI: 10.1097/rhu.0000000000001964
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Takayasu Arteritis in Rio de Janeiro, Brazil

Abstract: Objective Few population-based studies for Takayasu arteritis (TAK) have been performed, and Latin America prevalence/incidence data are unavailable. We aimed to understand TAK epidemiology in Rio de Janeiro City in 2020 (i.e., 6,747,815 inhabitants). Methods This was a cross-sectional fieldwork study where physicians who regularly followed TAK patients in public or private practices from Rio de Janeiro were invited to complete a REDCap survey. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…[6][7][8] In Rio de Janeiro, the prevalence of TAK has been estimated to be 16.9 cases per million people. 9 In contrast, TAK seems to be less frequent in Peru and comprised only 6.9% of the systemic vasculitides diagnosed in a Peruvian vasculitis referral center. 7 Takayasu arteritis is a difficult condition to manage because of the lack of accurate biomarkers to monitor disease activity, the possibility of subclinical vascular inflammation, and the paucity of randomized controlled trials to guide therapy.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…[6][7][8] In Rio de Janeiro, the prevalence of TAK has been estimated to be 16.9 cases per million people. 9 In contrast, TAK seems to be less frequent in Peru and comprised only 6.9% of the systemic vasculitides diagnosed in a Peruvian vasculitis referral center. 7 Takayasu arteritis is a difficult condition to manage because of the lack of accurate biomarkers to monitor disease activity, the possibility of subclinical vascular inflammation, and the paucity of randomized controlled trials to guide therapy.…”
mentioning
confidence: 89%
“…Whereas the epidemiology of TAK has not been characterized in most regions of Latin America, studies from Colombia and Southeast Brazil showed that TAK was the first and the second most frequent primary vasculitis diagnosed in tertiary hospitals, respectively 6–8 . In Rio de Janeiro, the prevalence of TAK has been estimated to be 16.9 cases per million people 9 . In contrast, TAK seems to be less frequent in Peru and comprised only 6.9% of the systemic vasculitides diagnosed in a Peruvian vasculitis referral center 7 …”
mentioning
confidence: 99%
“… 1 TAK is a rare disease with a worldwide distribution whose prevalence ranges from 0.9 cases/1 000 000 in the USA to 40 cases/1 000 000 in Japan 2 ; recently, the prevalence of TAK in Brazil was reported as 16.9 cases/1 000 000. 3 As a rare disease, the assessment of therapeutic agents for TAK by clinical trials is a challenge and only a few clinical trials have analysed available therapies. 4 5 Currently, the management of TAK is based mostly on the results of non-randomised case series.…”
Section: Introductionmentioning
confidence: 99%